2013
DOI: 10.1038/srep02838
|View full text |Cite
|
Sign up to set email alerts
|

MAL hypermethylation is a tissue-specific event that correlates with MAL mRNA expression in esophageal carcinoma

Abstract: MAL promoter hypermethylation was examined in 260 human esophageal specimens using real-time quantitative methylation-specific PCR (qMSP). MAL hypermethylation showed highly discriminative ROC curve profiles which clearly distinguished esophageal adenocarcinomas (EAC) from both esophageal squamous cell carcinomas (ESCC) and normal esophagus (NE). Both MAL methylation frequency and normalized methylation value (NMV) were significantly higher in Barrett's esophagus (BE), dysplastic BE, and EAC than in ESCC or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The analyses of the methylation status of MAL in normal cells and in a number of tumor specimens and tumor-derived cell lines indicate that the MAL CpG island is the subject of methylation, and that this epigenetic mechanism contributes to the downregulation of MAL gene expression in many cancers [ 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. The use of different methods—the sequencing of bisulfite-treated DNA, methylation-specific PCR (MSP), quantitative MSP, pyrosequencing, etc.…”
Section: Mal In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses of the methylation status of MAL in normal cells and in a number of tumor specimens and tumor-derived cell lines indicate that the MAL CpG island is the subject of methylation, and that this epigenetic mechanism contributes to the downregulation of MAL gene expression in many cancers [ 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. The use of different methods—the sequencing of bisulfite-treated DNA, methylation-specific PCR (MSP), quantitative MSP, pyrosequencing, etc.…”
Section: Mal In Cancermentioning
confidence: 99%
“…A significant correlation was found between MAL hypermethylation and Barrett’s esophagus segment length. MAL hypermethylation is, therefore, a common event in human esophageal adenocarcinoma but uncommon in squamous cell carcinoma [ 203 ]. In gastric cancer, hypermethylation of the proximal promoter region, but not of the distal region, is associated with better disease-free survival compared with that of patients with gastric tumors unmethylated or methylated only in the distal promoter region [ 199 ].…”
Section: Mal In Cancermentioning
confidence: 99%
“…Interestingly, also the expression of MAL (T-cell differentiation-related gene) was significantly reduced in both EAC and ESCC ( Table 2 ). MAL promoter hypermethylation correlating with decreased mRNA expression was reported [33] MAL is thought to be a novel suppressor gene [34] with diagnostic value in colorectal and esophageal cancers [35] . The protein has been localized to the endoplasmic reticulum of T-cells and is a candidate linker protein in T-cell signal transduction.…”
Section: Resultsmentioning
confidence: 98%
“…Our results indicated that there were 244 DEGs were screened via this method. Besides, many genes among DEGs such as MMP1 [ 11 ], MAGEA6 [ 12 ] and MAL [ 13 ] were closely associated with the progress of ESCC, which also implied the reliability of RRA.…”
Section: Discussionmentioning
confidence: 99%